Computed tomography in trauma patients using iterative reconstruction: reducing radiation exposure without loss of image quality - Kahn, Johannes; Grupp, Ulrich; Kaul, David; Böning, Georg; Lindner, Tobias; Streitparth, Florian (Acta radiologica (1987), 2016)
Rising numbers of computed tomography (CT) examinations worldwide have led to a focus on dose reduction in the latest developments in CT technology. Iterative reconstruction (IR) models bear the potential to effectively reduce dose while maintaining adequate image quality. To assess the impact of adaptive statistical iterative reconstruction (ASIR) technique on dose reduction and image quality in a dedicated whole body CT (WBCT) protocol for trauma patients. A total of 122 subjects with multiple trauma was prospectively included in our study. Subjects who had to undergo a WBCT following a severe trauma were randomly assigned to two different groups: Group A was examined with an ASIR protocol for the body series (n = 64), group B (n = 58) was examined using a standard filtered back projection (FBP) protocol. Image quality was assessed both quantitatively by calculating signal-to-noise ratio (SNR) and contrast-to-noise ratios (CNRs) and qualitatively by two observers who evaluated image quality using a 5-point scale system. Applied dose was analyzed as CTDIvol (mGy), total DLP (mGyxcm), and effective dose (mSv). Applied dose for the body series in group A was about 23% lower than in group B (P < 0.05). SNR and CNRs for different tissues were not significantly different. Subjective image quality ratings were excellent and showed no significant difference, with a high inter-reader agreement. ASIR contributes to a relevant dose reduction without any loss of image quality in a dedicated WBCT protocol for patients with multiple trauma.